Abnormal uterine bleeding in perimenopausal women: Correlation with sonographic findings and histopathological examination of hysterectomy specimens - Bharat Talukdar; Sangita Mahela (Wolters Kluwer Medknow Publications, 2016)
Background: Abnormal uterine bleeding (AUB) is a frequently encountered gynecologic complaint in perimenopausal woman and also the most common cause of hysterectomy in this age group. Objective: Evaluation of various clinical presentations of perimenopausal AUB and it is ultrasonographic and histopathological correlation of hysterectomy specimens. Materials and Methods: This study was carried out in the Department of Obstetrics and Gynaecology among perimenopausal women who underwent hysterectomy for AUB. The clinical presentations, ultrasonographic findings, and histopathological reports of hysterectomy specimen were correlated. Results: Among 103 number of hysterectomized cases for AUB, most of the patients were between 40 and 45 years of age (67.97%) and menorrhagia was the dominant clinical presentation. The majority (45.63%) of cases were diagnosed as fibroid uterus by ultrasonography with 89.13% sensitivity and 89.47% specificity. Histopathological reports of myometrium showed 44.66% fibromyoma, followed by 34.95% of the normal myometrium. Histopathology of endometrium revealed hyperplasia in the most cases (56.31%) where simple typical type was the predominant. Conclusion: Uterine fibroid was the leading cause of AUB and radiological, pathological evaluation correlated well to diagnose fibroid.